2019
DOI: 10.21873/invivo.11603
|View full text |Cite
|
Sign up to set email alerts
|

Beppu's Nomogram Score Is an Independent Prognostic Factor for Colorectal Liver Metastasis Receiving Perioperative Chemotherapy and/or Targeted Therapy

Abstract: Background/Aim: We investigated the impact of Beppu's nomogram on colorectal liver metastasis in patients receiving perioperative chemotherapy and/or targeted therapy. Patients and Methods: This study included 43 patients who underwent primary hepatic resection for colorectal liver metastasis at the Kanagawa Cancer Center from June 2006 to March 2011. The patients were classified as having a Beppu's nomogram score ≤9 (low-risk group) or ≥10 (high-risk group). The risk factors for the disease-free survival (DFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…This study developed and validated a prognosis model to predict the survival of CLM patients under the guidance of both the PROGRESS framework and the TRIPOD prediction research report for the first time. Previously developed nomograms (30)(31)(32)(33) could be more convincing if they expanded their sample size. We included as much population as possible from the SEER database, covering 35% population of the US.…”
Section: Discussionmentioning
confidence: 99%
“…This study developed and validated a prognosis model to predict the survival of CLM patients under the guidance of both the PROGRESS framework and the TRIPOD prediction research report for the first time. Previously developed nomograms (30)(31)(32)(33) could be more convincing if they expanded their sample size. We included as much population as possible from the SEER database, covering 35% population of the US.…”
Section: Discussionmentioning
confidence: 99%
“…Second, validation studies with internal and external cohorts are needed before the application of these scoring systems in general clinical settings. 9,10,[15][16][17][18] In the recent era, preoperative chemotherapy is often used for resectable and borderline resectable CRLMs. Therefore, the scoring systems developed so far need to be validated separately for patients who undergo upfront hepatectomy and for patients who undergo hepatectomy after neoadjuvant chemotherapy (NAC).…”
Section: Introductionmentioning
confidence: 99%
“…Although this nomogram is simple and convenient for clinical use, it is unclear whether it is useful in combination with recent advances in chemotherapy because it is a nomogram analyzed based on cases from 2000 to 2004. Higuchi et al validated this nomogram and demonstrated its efficacy [ 11 ]. However, this was confirmed in patients from 2006 to 2011.…”
Section: Introductionmentioning
confidence: 99%